Analysis of Factors Affecting Murabahah Financing on Sharia Commercial Banks in Indonesia 2012–2018 - Anggi Windu Safitri; Rimi Gusliana Mais (BPJP - STEI, 2019)
Abstract—This study aims to determine the effect of Capital Adequacy Ratio (CAR), Third Party Funds (DPK), Financing to Deposit Ratio (FDR), Non Performing Financing (NPF), and Return On Ratio (ROA) to Financing Murabaha at Islamic Commercial Banks in Indonesia for the 2012-2018 Period. There are ten samples in this study that meet the research criteria, namely BCA Syariah Bank, BRI Syariah Bank, BNI Syariah Bank, Mandiri Syariah Bank, Syariah Bukopin Bank, Panin Indonesia Syariah Bank, Jabar Banten Syariah Bank, Mega Syariah Bank, Muamalat Bank, Victoria Bank Sharia. This research method is quantitative with data processing tools usingEviews 9 and the analysis tool used was panel data regression analysis. The selected model is the modelFixed Effect which was tested by F test and t test, with a significance of 5%. The results of the study show that the ratio of Third Party Funds has a positive and significant effect on financing Murabaha which means that no matter how big the deposited DPK will affect any amount of financing Murabaha. Capital Adequacy Ratio, Financing to Deposit Ratio, Net Performing Financing, and Return on Assets does not affect financing Murabaha, which means that no matter how big the CAR, FDR, NPF, and ROA will not affect the distribution of capital adequacy, distribution of total loans, nonperforming financing and investment profits to Financing Murabaha.